2016
DOI: 10.1152/japplphysiol.01081.2015
|View full text |Cite
|
Sign up to set email alerts
|

Model-based stability assessment of ventilatory control in overweight adolescents with obstructive sleep apnea during NREM sleep

Abstract: Obstructive sleep apnea (OSA) involves the interplay of several different factors such as an unfavorable upper airway anatomy, deficiencies in pharyngeal muscle responsiveness, a low arousal threshold, and ventilatory control instability. Although the stability of ventilatory control has been extensively studied in adults, little is known about its characteristics in the pediatric population. In this study, we developed a novel experimental setup that allowed us to perturb the respiratory system during natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 65 publications
(66 reference statements)
4
14
1
Order By: Relevance
“…Similar to our study which showed no difference in LG between controls and those with SDB, previous studies have reported no difference in LG between overweight adolescents with and without OSA (OSA defined as OAHI >5 events/h) 24 or between clusters of term and preterm born children aged 6 months to 7 years at various degrees of risk for OSA (OSA defined as OAHI >2 events/h). 23 In addition, it has also been reported that there was no difference in ventilatory responses to hypoxia and hypercapnia (a component of LG) in children with and without OSA during both wakefulness 34 and sleep.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our study which showed no difference in LG between controls and those with SDB, previous studies have reported no difference in LG between overweight adolescents with and without OSA (OSA defined as OAHI >5 events/h) 24 or between clusters of term and preterm born children aged 6 months to 7 years at various degrees of risk for OSA (OSA defined as OAHI >2 events/h). 23 In addition, it has also been reported that there was no difference in ventilatory responses to hypoxia and hypercapnia (a component of LG) in children with and without OSA during both wakefulness 34 and sleep.…”
Section: Discussionsupporting
confidence: 90%
“…Contrary to what has been described in adults with OSA who have an increase in LG, our pediatric population with OSA did not show a significant difference in LG compared with that in healthy control subjects. Similar observations were made in studies of overweight adolescents (24) and obese women (57), where subjects with OSA also had high PG, low CG, and a low LG. These data suggest that different mechanisms of ventilatory control abnormalities may lead to respiratory instability and OSA.…”
Section: Discussionsupporting
confidence: 82%
“…Estimations of LG, PG, and CG were extracted from the spontaneous sigh recordings by using an adaptation of the technique employed by Nava-Guerra and colleagues (24). A slight modification extending the frequencies for periodic breathing between 0.01 and 0.125 Hz was done to account for breathing frequency being considerably faster in young children than in adolescents.…”
Section: At a Glance Commentarymentioning
confidence: 99%
“…Similar to our study, the authors estimated LG from the ventilatory response that followed spontaneous sighs. Although they utilized a different technique to estimate LG, the mean values in their study (~0.28) were identical to those of our low CAI group. This may suggest that the high LG observed in our high CAI group may be moving into an ‘abnormal’ range for this age group, or at least making them more prone to ventilatory instability in response to a perturbation.…”
Section: Discussionsupporting
confidence: 58%